Factors that influence the selection of restaurants (consumers), from the historic center of Puebla (GEON Journal (Management, Organizations and Business), 2017)
This research aimed to investigate the main factors that are taken into account by consumers in restaurants, to select them. This study specifically explore the behavior of consumers who attends at restaurants located in the dowtown of Puebla city, so the researches identified significant items as "flavor of food, quality of service, recommendations from family and friends and social network advertising" that are crucial to generate a positive behavior of purchase by the customer's gastronomic company. At the same time we also inquired about the degree of use of administrative tools by restaurant owners, we found that only 13 percent of owners have a written business plan to guide the activities of the restaurant.Therefore in the concluding section, a training strategy is suggested to improve the management skills and encourage a focus on the determinants for customers and generate a better "image" that results in successful companies.
Keywords: consumer behavior; restaurants; marketing